Reactions of public school administrators and supervisors of Manila and Quezon City to certain educational ideas to improve Philippine education - Sarmenta, Josefina (Eugenio) 1917- (s.n.], 1973)
Reactions were elicited on the project recommendations of the Presidential Commission to Survey Philippine Education in the areas of Elementary and Secondary Education, Higher Education, Vocational/Technical Education and Educational Administration and Finance. There was strong agreement on science equipment projects, secondary curriculum revision, student informative service, pre-employment training and guidance centers, entrance policies of teacher-training institutions, and student scholarship, loans and other forms of assistance to all students. All other educational ideas received mean values equivalent to "agree". Respondents 60 years old and above and those with 30 or more years in the service gave higher mean values where the majority gave lower mean values.